Investigation of Prognostic Markers of Lung Adenocarcinoma Based on Tumor Metabolism-Related Genes - Zhang, Chong; He, Zhehao; Cheng, Ling; Cao, Jinlin (Frontiers in Genetics, 2021)
Lung adenocarcinoma (LUAD) is a prevalent cancer killer. Investigation on potential prognostic markers of LUAD is crucial for patient’s postoperative planning. LUAD-associated datasets were acquired from Gene Expression Omnibus (GEO) as well as The Cancer Genome Atlas (TCGA). LUAD metabolism-associated differentially expressed genes were obtained, combining tumor metabolism-associated genes. COX regression analyses were conducted to build a 5-gene prognostic model. Samples were divided into high- and low-risk groups by the established model. Survival analysis displayed favorable prognosis in the low-risk group in the training set. Favorable predictive performance of the model was discovered as hinted by ROC. Survival analysis and ROC analysis in the validation set held an agreement. GSEA enrichment analysis, tumor mutation bearing (TMB) and immune infiltration differential analysis were performed. The two groups displayed differences in Glycolysis gluconeogenesis, P53 signaling pathway, etc. High-risk group showed higher TP53 mutation frequency as well as TMB. The low-risk group displayed higher immune activity along with immune score. Together, this study casts light on further development of novel prognostic markers for LUAD.